Meta Analisis Pengembangan Assesment Kelayakan Sistim Pembangkit Tenaga Air - suryadimal suryadimal (Universitas Negeri Padang, 2018)
Abstract-This study aims to determine the feasibility assessment of hydroelectricity to feasibility studies that have been conducted in various developing and developed countries. In a feasibility study usually consider various important aspects such as technical and non technical aspects that will affect the productivity of a feasibility study.Methododologi research based on the meta-analysis method, in which the analysis is based on a review of a number of research results on similar issues in the case of a feasibility assessment of the power plant system. Approaches are based on journal articles and research reports that are taken based on their compatibility with the theme of research. The technical aspects used are hydraulic and civil aspects, mechanical and electrical aspects, while non technical aspects are economic, social and cultural aspects. So with the development of this feasibility rating model can be a reference for developers, government and investors to decide the feasibility of a power plant investment Keywords: Assessment Feasibility, Hydropower, Power Plant, Feasibility Study, Meta analysis